The long-term effects of probiotics in the therapy of ulcerative colitis: A clinical study - Palumbo, Vincenzo Davide; Romeo, Marcello; Marino Gammazza, Antonella; Carini, Francesco; Damiani, Provvidenza; Damiano, Giuseppe; Buscemi, Salvatore; Lo Monte, Attilio Ignazio; Gerges-Geagea, Alice; Jurjus, Abdo; Tomasello, Giovanni (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2016)
AIM: Intestinal dysbiosis seems to be the leading cause of inflammatory bowel diseases, and probiotics seems to represent the proper support against their occurrence. Actually, probiotic blends and anti-inflammatory drugs represent a weapon against inflammatory bowel diseases. The present study evaluates the long-term (2 years) effects of combination therapy (mesalazine plus a probiotic blend of Lactobacillus salivarius, Lactobacillus acidophilus and Bifidobacterium bifidus strain BGN4) on ulcerative colitis activity. METHOD: Sixty patients with moderate-to-severe ulcerative colitis were enrolled: 30 of them were treated with a single daily oral administration of mesalazine 1200 mg; 30 patients received a single daily oral administration of mesalazine 1200 mg and a double daily administration of a probiotic blend of Lactobacillus salivarius, Lactobacillus acidophilus and Bifidobacterium bifidus strain BGN4. The treatment was carried out for two years and the clinical response evaluated according to the Modified Mayo Disease Activity Index. RESULTS: All patients treated with combination therapy showed better improvement compared to the controls. In particular, the beneficial effects of probiotics were evident even after two years of treatment. CONCLUSIONS: A long-term treatment modality of anti-inflammatory drugs and probiotics is viable and could be an alternative to corticosteroids in mild-to moderate ulcerative colitis.
Keywords: dospělí; Bifidobacterium bifidum; Double-Blind Method; kombinovaná farmakoterapie; lactobacilli; Humans; ulcerózní kolitida; Analysis of Variance; Drug Therapy, Combination; lidé středního věku; Anti-Inflammatory Agents, Non-Steroidal; Middle Aged; Colitis, Ulcerative; antiflogistika nesteroidní; mužské pohlaví; bifidobacteria; ulcerative colitis; Adult; dvojitá slepá metoda; Ligilactobacillus salivarius; výsledek terapie; inflammatory bowel diseases; analýza rozptylu; Treatment Outcome; ženské pohlaví; Mesalamine; Probiotics; mesalamin; microbiota; Lactobacillus acidophilus; lidé; Lactobacillus salivarius; Aged; senioři; Male; probiotika; Female